Modelling Extreme Stock Market Risk with Peaks Over Threshold-Value at Risk and APARCH Specifications - Aulia Khairani Hutabarat; Ayu Sofia; Muklas Rivai (Jurusan Matematika FMIPA UNM, 2026)
The capital market plays an important role in a country's economy. Through the capital market, investors can also grow their wealth by investing in stocks, bonds, or other instruments. Investing in stocks in the capital market has high profit potential, but also carries significant volatility risks. One company that experienced significant volatility was PT Indofood Sukses Makmur Tbk., as in 2020 when the COVID-19 pandemic caused extreme volatility in global and local markets. Therefore, risk management is necessary to minimize risks using the Value at Risk method.This study also aims to analyze the risk of investing in PT Indofood Sukses Makmur Tbk. shares using the VaR method with APARCH modeling and the POT approach. The data used are daily closing prices from March 2020 to June 2025. The results show that the best model for forecasting is APARCH(1,1) with a better forecasting accuracy than the naive forecast, as indicated by the MASE value of 0,6131. The VaR estimate indicates that the longer the forecasting period and the higher the confidence level used, the higher the VaR value. This indicates that the extreme risk is higher for the next ten periods. The validity test (backtesting) also confirms that the VaR estimation results are accurate for the long term at a significance level of 1%, 5% and 10%.